2017
DOI: 10.1182/blood-2016-10-746347
|View full text |Cite
|
Sign up to set email alerts
|

NOX5 and p22phox are 2 novel regulators of human monocytic differentiation into dendritic cells

Abstract: Dendritic cells (DCs) are a heterogeneous population of professional antigen-presenting cells and are key cells of the immune system, acquiring different phenotypes in accordance with their localization during the immune response. A subset of inflammatory DCs is derived from circulating monocytes (Mo) and has a key role in inflammation and infection. The pathways controlling Mo-DC differentiation are not fully understood. Our objective was to investigate the possible role of nicotinamide adenine dinucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 62 publications
2
58
2
2
Order By: Relevance
“…The early NOX5 studies demonstrated that mRNA of NOX5 is expressed in pachytene spermatocytes of the testis and in B‐ and T‐lymphocyte‐rich areas of the lymph nodes and spleen (Bánfi et al., ; Cheng et al., ). Whether NOX5 is expressed and functionally active in circulating phagocytic cells has been debated, because original studies failed to identify NOX5 in peripheral lymphocytes, whereas recent studies indicate that NOX5 is expressed in human monocytes and macrophages (Manea et al., ; Marzaioli et al., ) and that NOX5 regulates human monocyte differentiation into dendritic cells (Marzaioli et al., ). However, most of those studies were performed in monocyte/macrophage leukaemia cell lines (Marzaioli et al., ), and the physiological role of neutrophil NOX5 is unclear.…”
Section: Expression Of Nox5 In Physiological and Pathological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early NOX5 studies demonstrated that mRNA of NOX5 is expressed in pachytene spermatocytes of the testis and in B‐ and T‐lymphocyte‐rich areas of the lymph nodes and spleen (Bánfi et al., ; Cheng et al., ). Whether NOX5 is expressed and functionally active in circulating phagocytic cells has been debated, because original studies failed to identify NOX5 in peripheral lymphocytes, whereas recent studies indicate that NOX5 is expressed in human monocytes and macrophages (Manea et al., ; Marzaioli et al., ) and that NOX5 regulates human monocyte differentiation into dendritic cells (Marzaioli et al., ). However, most of those studies were performed in monocyte/macrophage leukaemia cell lines (Marzaioli et al., ), and the physiological role of neutrophil NOX5 is unclear.…”
Section: Expression Of Nox5 In Physiological and Pathological Conditionsmentioning
confidence: 99%
“…Whether NOX5 is expressed and functionally active in circulating phagocytic cells has been debated, because original studies failed to identify NOX5 in peripheral lymphocytes, whereas recent studies indicate that NOX5 is expressed in human monocytes and macrophages (Manea et al, 2015;Marzaioli et al, 2017) and that NOX5 regulates human monocyte differentiation into dendritic cells (Marzaioli et al, 2017). However, most of those studies were performed in monocyte/macrophage leukaemia cell lines (Marzaioli et al, 2017), and the physiological role of neutrophil NOX5 is unclear. In the developing zebrafish, Nox5 is expressed throughout the CNS and, together with Nox2, it might be important in neurodevelopment and regeneration (Weaver et al, 2018;Weaver, Leung, & Suter, 2016).…”
Section: Expression Of Noxin Physiological and Pathological Conditionsmentioning
confidence: 99%
“…Human embryonic kidney cell line (HEK 293 cells) or any other cell line with very low or no endogenous expression of NOX/DUOX enzymes.24. DMEM medium, high glucose (4.5 g/L), containing 10% FBS, or similar 25…”
mentioning
confidence: 99%
“…In humans, Nox5 is broadly expressed in blood vessels, primarily smooth muscle cells, microvascular endothelial cells, fibroblasts [6,8,9] but also in testis [8] and spleen, specifically in monocytes, macrophages [7,10], B- and T-cells [11]. To mimic the physiological human expression pattern of NOX5 in mice, we created a mouse line called NOX5 KI (knock-in) bearing the human NOX5 gene in the Hprt locus and under control of the Tie2 promoter (Fig 1A-B).…”
Section: Resultsmentioning
confidence: 99%